CONUT Score Predicts Early Morbidity After Liver Transplantation: A Collaborative Study - Spoletini, Gabriele; Ferri, Flaminia; Mauro, Alberto; Mennini, Gianluca; Bianco, Giuseppe; Cardinale, Vincenzo; Agnes, Salvatore; Rossi, Massimo; Avolio, Alfonso Wolfango; Lai, Quirino (Frontiers in Nutrition, 2022)
Introduction: Liver transplantation (LT) is burdened by the risk of postoperative morbidity. Identifying patients at higher risk of developing complications can help allocate resources in the perioperative phase. Controlling Nutritional Status (CONUT) score, based on lymphocyte count, serum albumin, and cholesterol levels, has been applied to various surgical specialties, proving reliable in predicting complications and prognosis. Our study aims to investigate the role of the CONUT score in predicting the development of early complications (within 90 days) after LT. Methods: This is a retrospective analysis of 209 patients with a calculable CONUT score within two months before LT. The ability of the CONUT score to predict severe complications, defined as a Comprehensive Complication Index (CCI) ≥42.1, was examined. Inverse Probability Treatment Weighting was used to balance the study population against potential confounders. Results: Patients with a CCI ≥42.1 had higher CONUT score values (median: 7 vs. 5, P-value<0.0001). The CONUT score showed a good diagnostic ability regarding post-LT morbidity, with an AUC=0.72 (95.0%CI=0.64-0.79; P-value<0.0001). The CONUT score was the only independent risk factor identified for a complicated post-LT course, with an odds ratio=1.39 (P-value<0.0001). The 90-day survival rate was 98.8% and 87.5% for patients with a CONUT score <8 and ≥8, respectively. Conclusions: Pre-operative CONUT score is a helpful tool to identify patients at increased post-LT morbidity risk. Further refinements in the score composition, specific to the LT population, could be obtained with prospective studies.